A piezoelectric energy harvesting concept for an energy-autonomous instrumented total hip replacement. (22nd October 2020) - Lange, Hans-E; Hohlfeld, Dennis; Bader, Rainer; Kluess, Daniel
Abstract: To improve the clinical outcome of total hip replacements (THRs), instrumented implants with sensory functions for implant monitoring and diagnostics or actuators for therapeutic measures are a promising approach. Therefore, an adequate energy source is needed. Batteries and external power supplies bring shortcomings e.g. limited lifetime or dependency on external equipment. Energy harvesting has the clear benefit of providing continuous and independent power for fully autonomous implants. Our present study evaluates by means of finite element analysis (FEA) the capabilities of a concept of a piezoelectric energy harvesting system (ring shaped multilayer piezoelectric element of 5 mm diameter and 2.5 mm height) integrated in a femoral hip stem. The deformations from a modified load-bearing implant are used to generate electric power for various instrumentation purposes. Besides the expected amount of converted energy, the influence on the stress distribution of the instrumented implant is analysed. The results show that the local stress increase for the modified implant geometry does not exceed the stress of the original reference model. The maximum generated open circuit voltage of 11.9 V can be processed in standard energy harvesting circuitry whereas an average power output amounts up to 8.1 µ W. In order to increase the electric power in an upcoming design optimization, a sensitivity analysis is performed to identify the most important influencing parameters with regard to power output and implant safety.